1989
DOI: 10.1111/j.1600-0447.1989.tb08580.x
|View full text |Cite
|
Sign up to set email alerts
|

Explorative single‐blind study on the sedative and hypnotic effects of buspirone in anxiety patients

Abstract: In this single-blind study the sedative and hypnotic properties of buspirone, a nonbenzodiazepine anxiolytic, were investigated in 8 anxious outpatients. Polysomnographic recordings were gathered during baseline, at the start of active medication, after 3 weeks of treatment and one night after discontinuing treatment. Daytime alertness was measured using the Multiple Sleep Latency Test and performance tests. The effects of buspirone on sleep structure were minimal and of no clinical consequence. Subjectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Flesinoxan was responsible for a lengthening in REM latency which supports its antidepressant potential. A single blind study using buspirone 5 mg in eight anxious outpatients also found an increase in REM sleep latency but at a statistically nonsignificant level; by the end of the 3-week trial, all patients had returned to baseline values (De Roeck et al, 1989). These differences between flesi- noxan and buspirone copld also result from the distinction between these compounds in their 5-HTlA agonistic properties.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Flesinoxan was responsible for a lengthening in REM latency which supports its antidepressant potential. A single blind study using buspirone 5 mg in eight anxious outpatients also found an increase in REM sleep latency but at a statistically nonsignificant level; by the end of the 3-week trial, all patients had returned to baseline values (De Roeck et al, 1989). These differences between flesi- noxan and buspirone copld also result from the distinction between these compounds in their 5-HTlA agonistic properties.…”
Section: Discussionmentioning
confidence: 94%
“…Flesinoxan, a full post-synaptic 5-HTlA agonist, could exhibit a faster onset of action and/or a higher antidepressant efficacy compared to partial 5-HTl A agonist such as gepirone, ipsapirone, and buspirone. Flesinoxan was initially developed as an antihypertensive drug (Wouters er al., 1988); clinical trials however did not support its antihypertensive efficacy but showed an excellent tolerance (De Voogd and Prager, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In randomized, double-blind placebo-controlled trials with healthy subjects, buspirone suppressed REM sleep (Ware et al, 1994; and increased sleep fragmentation . In a single-blind study of anxious patients, buspirone improved subjective sleep quality compared to baseline placebo but had no clinically significant effect on sleep macroarchitecture (De Roeck et al, 1989). In a single-blind study of anxious patients, buspirone improved subjective sleep quality compared to baseline placebo but had no clinically significant effect on sleep macroarchitecture (De Roeck et al, 1989).…”
Section: Anxiolytics (Not Classified Elsewhere)mentioning
confidence: 92%
“…Buspirone has no significant effect on a sleep electroencephalogram (EEG) when given either on a single occasion or for three weeks in anxious patients, at doses of 20 mg/day, or on abrupt withdrawal after that length of time (De Roeck et al, 1989). While buspirone lacks immediate hypnotic properties per se, three out of four double-blind studies in which a sleep questionnaire was used showed relief of insomnia that was secondary to anxiety, during treatment with buspirone.…”
Section: Sleepmentioning
confidence: 99%